Animal biosynthesis of complex polyketides in a photosynthetic partnership - Joshua P. Torres (Nature Portfolio, 2020)
Complex polyketides are usually produced by microbes, whereas the origin of polyketides found in animals remained unknown. This study shows that sacoglossan animals, such as sea slugs, employ fatty acid synthase-like proteins to produce microbe-like polyketides.